Analysis of STEAM-Based TPACK Integrated Activities in Elementary School Thematic Books - Idam Ragil Widianto Atmojo; Dwi Yuniasih Saputri; Alifia Khaerunnisa Fajri (Mimbar Sekolah Dasar, 2022)
Technological, Pedagogical, and Content Knowledge (TPACK) can collaborate with the Science Technology Engineering Art Mathematics (STEAM) approach. STEAM is also essential for students to improve their ability and skills to operate and produce science and technology-based products, supported by the TPACK abilities of educators to develop quality technology-based learning. In this study, there were 26 items of integrated TPACK and STEAM activities, with the most findings being content knowledge, as much as 27.50% for science. The second-highest finding was the integration of pedagogical knowledge, as much as 24%. Furthermore, the third most common finding, 17.40%, was the integration of technological knowledge with art and pedagogical content knowledge with art, while 10% of activities integrated content knowledge with art. The last finding found the integration of pedagogical knowledge with science of 3.4%. However, all indicators did not appear mathematical. In addition, the most common finding was the integration of art and pedagogical content knowledge, as much as 34.60%. The percentage of activities integrating engineering and content knowledge was 27%, which was the highest finding. In this case, one activity allows more than one integration.